Assessment of disease activity and progression in Takayasu's arteritis - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2011)
Takayasu's arteritis (TA) is a rare, chronic panarteritis of the aorta and its major branches presenting commonly in young ages. Physical examination findings, presence of constitutional features, elevated acute-phase reactants, and new vessel involvement in imaging are major features of an active disease. However, assessment of disease activity and damage in TA is problematic given the chronic, indolent disease course and lack of specific laboratory and imaging findings. Although CT, MRI, and FDG-PET are commonly used imaging modalities, their lack of specificity to discriminate active disease from damage, limit their usefulness in routine practice. Two recently introduced multi-systemic clinical assessment tools, the DEI.Tak and the ITAS (both derived from BVAS), seem to be helpful in assessing disease activity and damage in TA. However, physician's global assessments of disease activity and decisions regarding treatments are still strongly influenced by changes in the acute-phase response and imaging. A comprehensive approach to both systemic and vascular features of TA to define a validated set of outcome measures for use in clinical trials and clinical practice is clearly needed. The OMERACT Vasculitis Working Group has taken on this task and has embarked on a research agenda to advance outcome measure development in TA.
Keywords: vasculitis; assessment; outcomes; Takayasu's arteritis; LARGE-VESSEL VASCULITIS; QUALITY-OF-LIFE; NECROSIS FACTOR THERAPY; FOLLOW-UP; SYSTEMIC VASCULITIDES; CELL ANTIBODIES; CT ANGIOGRAPHY; F-18-FDG PET; DIAGNOSIS; MANAGEMENT